Long-term follow-up of chronic spinal cord stimulation for medically intractable orthostatic tremor - Blahak, Christian; Sauer, Tamara; Bäzner, Hansjörg; Wolf, Marc; Hennerici, Michael G. (Journal of neurology, 2016)
Orthostatic tremor (OT) is a rare form of tremor occurring in the legs when standing upright. Medical treatment frequently is unsatisfactory, thus in selected cases, surgical treatment, such as spinal cord stimulation (SCS) or thalamic deep brain stimulation has been proposed. We report the long-term results (follow-up (FU) 34-133 months) of SCS in four patients with medically intractable OT. Outcome was assessed by recording the time tolerated to stand still pre- and post-operatively and by a patient self-rating (PSR) scale (0 = poor to 6 = excellent). Furthermore, surface electromyography (EMG) recordings of different leg muscles were performed to estimate tremor activity with and without SCS post-operatively. With chronic SCS, all four patients showed an improvement of unsteadiness occurring in the presence of stimulation-induced paraesthesia of the legs. The mean standing time improved from 51 s (SD 47 s, range 4-120 s) pre-operatively to 220 s (SD 184 s, range 10-480 s) with SCS at last available FU. Tremor activity in the EMG of the anterior tibial muscle was reduced by 30-60 % with SCS compared with off SCS. PSR score was 4 or 5 in three patients and 3 in the other. In conclusion, SCS is an effective long-term treatment option in patients with otherwise intractable OT.
Gesehen am 18.04.2019